First-principles calculations on structural, electronic and optical oroperties of Ce-, Nd- and Er-doped TiO2 - M. H., Samat (Universiti Malaysia Perlis (UniMAP), 2021)
Link to publisher's homepage at http://ijneam.unimap.edu.my